Natural and Human Influences on Marine Processes in Patagonian Subantarctic Coastal Waters - Iriarte, José L. (Frontiers in Marine Science, 2018)
Projections for high-latitude polar and subpolar environments show some of the largest climate changes on Earth in coming decades (IPCC, 2014). Patagonia (41–55°S), a vast pristine system whose economic and societal well-being depends on coastal resources ( 80% of people live near-shore; the coastal economy provides >40,000 jobs), is experiencing various simultaneous socio-environmental perturbations. In this new scenario, overlapping natural variability (interannual - seasonal dynamics) and human-induced environmental changes (global change) are major drivers influencing the marine food web structure and functions. Evidence of large environmental changes has been detected in the Patagonia marine system through a) regional-scale climatic-oceanographic anomalous events, b) interannual hydrological changes in freshwater river inputs (watersheds into fjords), and c) more frequent coastal and oceanic biological outbreaks (harmful algal blooms). Those changes have highly uncertain effects for the basic functionalities, structure, and feedback responses of coastal systems and their coupling with hydrological (e.g., river streamflow) or biogeochemical (e.g., carbonate system) processes. The northern Patagonian fjords system is hypothesized to act as an indicator of large-scale climate change given strong environmental variability. This, combined with regional climatic-oceanographic events (e.g., El Niño Southern Oscillation, Southern Annular Mode) and effects of local anthropogenic-activities (e.g., nutrient fluxes from extensive aquaculture, land change due to forestry) may impact surface water chemical and physical properties, destabilizing biological productivity and chemical coastal processes. This synthesis of results of systemic-sensitive chemical and biological variables may be useful for managers and for preventing socio-environmental impacts from increasing natural and anthropogenic phenomena in Chile's southern coastal system.